2020
DOI: 10.3168/jds.2020-18704
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lactic acid bacteria from human milk

Abstract: Human milk is the main source of nutrition for infants and the transmission of various microorganisms. The lactic acid bacteria (LAB) in breast milk allow for the establishment of the gut microflora of infants. In this study, we aimed to assess the probiotic potential of LAB strains isolated from breast milk of healthy Chinese women. Two strains, Lacticaseibacillus rhamnosus (formerly Lactobacillus rhamnosus) LHL6 and LHL7, were selected and identified through morphology observation, Gram staining, and 16S rDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Numerous studies have shown that probiotics may adhere and survive in the gastrointestinal tract of humans and animals, and contribute to maintaining a microecological balance, promoting digestive and metabolic processes, as well as modulating the immune response, thereby enhancing host immunity, and improving human and animal health [ 9 , 13 , 26 ]. However, because the effectiveness of probiotics is species or strain dependent, they should meet a series of characteristics, such as safety (antimicrobial susceptibility and hemolytic activity), functional (acid and bile salt tolerance and intestinal mucosa adhesion), as well as beneficial (antagonistic activity, growth, and acid-producing ability) characteristics [ 12 , 13 , 17 ]. Hence, in this study, we focused on beneficial strains with potential probiotic properties isolated from cattle-yak milk using a series of in vitro tests, and the whole-genome sequencing was performed to reveal their potential biological functions and information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that probiotics may adhere and survive in the gastrointestinal tract of humans and animals, and contribute to maintaining a microecological balance, promoting digestive and metabolic processes, as well as modulating the immune response, thereby enhancing host immunity, and improving human and animal health [ 9 , 13 , 26 ]. However, because the effectiveness of probiotics is species or strain dependent, they should meet a series of characteristics, such as safety (antimicrobial susceptibility and hemolytic activity), functional (acid and bile salt tolerance and intestinal mucosa adhesion), as well as beneficial (antagonistic activity, growth, and acid-producing ability) characteristics [ 12 , 13 , 17 ]. Hence, in this study, we focused on beneficial strains with potential probiotic properties isolated from cattle-yak milk using a series of in vitro tests, and the whole-genome sequencing was performed to reveal their potential biological functions and information.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA of selected strains was extracted using a DNA extraction kit (Omega Bio-tek, Norcross, GA, USA) according to the manufacturer’s instructions. The quality of the purified DNA samples was checked using an Agilent 2100 Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA), and further PCR-amplified using universal primers for bacteria [ 17 ]. The PCR products were identified by 16S rRNA gene sequencing (Tsingke Biotech, Xi’an, Shaanxi, China), and by consulting the NCBI BLAST sequence database ( (accessed on 25 October 2021)).…”
Section: Methodsmentioning
confidence: 99%
“…The acid and bile tolerance of isolates were checked according to the methods described previously with minor modifications ( 11 ). Acid tolerance was examined in MRS broth and adjusted to a final pH of 2.5 using 1N HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Human milk is the main source of Lactic Acid Bacteria (LAB); LAB indicated a protective effect against rotavirus and TGEV [47]. Moreover, two strains Lacticaseibacillus rhamnosus LHL6 and LHL7 have significant probiotic property in breast milk [48]. Administration of L. rhamnosus showed a beneficial effects on the protection against enteric viruses in vivo [49].…”
Section: Major Effects Of Probiotic-containing and Fermented Foods On Viral Infectionsmentioning
confidence: 99%